Influence of cutting length and environment on the growth of coffee seedlings obtained by rooting - Humberto Oliveira, Diego; Pereira Baliza, Danielle; Teruel Rezende, Tiago; Pereira de Carvalho, Samuel; José Guimarães, Rubens (Coffee Science - ISSN 1984-3909, 1970)
As a contribution to the establishment of a suitable methodology for producing Coffea arabica L. seedlings through vegetative propagation, the aim of this work was to study the influence of cutting length and environment on the growth of coffee seedlings obtained by rooting. The experiment was conducted in a completely randomized design, arranged in a 5x2 factorial scheme corresponding to five cutting lengths (3,5 - 5,2; 5,2 - 5,5; 5,5 - 6,3; 6,3 - 6,7 and 6,7 - 8,5 cm) and two environments (greenhouse-shade “sombrite” and greenhouse). The experiment was carried out for 90 days. The following variables were assessed: plant height, number of knots and paired leaves, main root length and plant dry matter. From the results it was concluded that longer cuttings managed in the greenhouse-shade “sombrite” system provided a better development of the seedlings.